Estudo da interface entre blocos cerâmicos e argamassas de chapisco - Carvalho, Denizard Paulo (2016)
The analysis of adhesion mechanisms between mortar lining and porous substrates has been the target of innumerous researchers due to its importance in ensuring system performance. Based on the theoretical reference of the topic, this work of experimental nature aimed to analyze the influence of the superficial topography of ceramic blocks in bonding slurry mortars and their relationship with the set of characteristics of fine aggregates that make up slurry mortars. Initially, the substrates and component materials of the mortars were characterized according to the Brazilian Association of Technical Standards; afterwards, characterization tests of fresh and hardened mortars were carried out. In the testing phase, the blocks received the slurry mortars. The experimental variables studied were: three types of ceramic blocks (ceramic sealing block with smooth surfaces, ceramic sealing block with horizontal grooved surfaces, and ceramic sealing block with vertical grooved surfaces); and two types of slurry mortars (one was prepared with coarse sand and the other with medium sand). Thus, six interfaces were evaluated through aspects of bonding strength and permeability and absorption by the pipe method. In order to observe the extent of adhesion and involvement of the grains of sand through the paste of the slurry mortars, interface analyses were conducted through observation by magnifying glass and petrographic microscope. The characteristics of the sands that influence the performance of fresh and hardened slurry mortars were analyzed, with emphasis on the textural parameters of the sands, which were evaluated with the aid of petrographic analysis. Results showed that there is direct correlation between the extent of adhesion provided by the grooves of the blocks, and bond tensile strength, made possible by the fluid nature of the slurry mortar. Therefore, this indicates the strong influence of the type of ceramic block on results of bond strength. On the other hand, the study of the characteristics of the sands, represented mainly by the granulometric composition, density, unitary mass, void content, degrees of roundness and sphericity, and mineralogy, proved to be useful in order to understand the role of the fine aggregates in the performance of the slurry mortar. Additionally, we observed that the tensile bonding strength was higher for the slurry mortars with coarse sand than with medium sand, when comparing the same type of block, although the tests have pointed to non-significant differences. This fact can be explained by the small difference between some of the characteristics of the sand used; however, the coarse sand studied seems to provide greater integration of the grains involved by the mortar paste, which was indicated by the degree of roundness. Moreover, it was also possible to observe direct relations in achieving results when comparing the permeability and absorption by the pipe method with the initial rate of absorption test (IRA) and extended IRA test. The final observation is that the basic treatment using slurry mortar can provide several benefits: increased roughness of the base, increased tensile bonding strength, adjustment of the suction capacity. This way, it was possible to homogenize the absorption of water by the substrate, thus avoiding different screeding times and performance for the lining layer. Thus, the treatment of the base with the use of slurry mortar can increase the performance and durability of the mortar lining.